RAMET HARVESTING AND VEGETATIVE GROWTH OF AECHMEA NUDICAULIS (L.) GRISEB. (BROMELIACEAE) - ANACLETO, Adilson; NEGRELLE, Raquel Rejane Bonato (Scientia Agraria, 2009)
The bromeliads are monocotyledon plants of the Bromeliaceae family, consisting of more than 1500 species only in Brazil, with the Atlantic Forest being its main habitat. The littoral of Paraná, is one of the regions in the Atlantic Forest, where the extrativism of bromeliads for commercial purposes reaches the highest intensity in Brazil. Among the most harvested species Aechmea nudicaulis is distinguished from the others. To evaluate the impact of extractivism on this species, it was selected forty parental units of A. nudicaulis which were submitted to different types of ramet harvesting and monitored bi-monthly to evaluate the effect of harvesting on their vegetative growth (sprouting). The extracted ramets were planted and monitored to measure leaf production, height, and time necessary to reach commercial size. The extractivism did not promote a visible effect on parental units sprouting. The ramets that were bigger than 1/3 of the parental unit’s size, took less time (96 days) to reach commercial size (≥ 35 cm high and four leaves), therefore, this type of ramet reveals itself as the best option of usage in cultivation systems.